Advances in Knowledge Representation, Logic Programming, and Abstract Argumentation - Eiter, Th (Springer, 2015)
This Festschrift is published in honor of Gerhard Brewka on the occasion of his 60th birthday and contains articles from fields reflecting the breadth of Gerd's work. The 24 scientific papers included in the book are written by close friends and colleagues and cover topics such as Actions and Agents, Nonmonotonic and Human Reasoning, Preferences and Argumentation.